Remoção do Corante Têxtil Turquesa de Remazol Empregando Aguapé (Eichhornia crassipes) como Adsorvente - Holanda, Carlos Alexandre; Souza, Janilson Lima; dos Santos, Clayane Carvalho; dos Santos Silva, Hildo Antônio; Santana, Sirlane Aparecida Abreu; Costa, Maria Célia Pires; Schultz, Mario Sergio; Bezerra, Cícero Wellington Brito (Orbital: The Electronic Journal of Chemistry, 2015)
In this work, the efficient removal of Remazol Turquoise textile dye onto water hyacinth (Eichhornia crassipes) from aqueous solutions was investigated by batch method. The water hyacinth was collected, washed, dried, crushed and treated with a 0.25 mol L-1 HNO3, at 50 °C and by 24 h. Parameters such as pHpzc, pH effect, contact time and temperature were considered. The kinetic and adsorption data were analyzed by using the Lagergren, Ho, Zeldowitsch (Elovich), and Weber-Morris models, and Langmuir, Freundlich, Tempkin, Redlich-Peterson, Sips and multilayers isotherm models, respectively. The best fitting modeling were Ho (50 mg L-1), Elovich (1000 mg L-1) and Sips. The thermodynamic parameters (ΔHads, ΔSads and ΔGads) and desorption tests showed that adsorption mechanism is dependent on several adsorbate/surface interactions.DOI: http://dx.doi.org/10.17807/orbital.v7i2.622